PROSES PERCERAIAN DALAM PERSPEKTIF MARTIN BUBER - Imanuel Teguh Harisantoso (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
Divorce in Indonesia is increasing from time to time. This is an indisputable social fact. This research will analyze how the divorce process occurs and how a husband or wife sees their partner from Martin Buber's perspective through a philosophical approach. Divorce is a process leading to separation. Starting from a crisis and prolonged domestic conflict, in the end, it brings a new "perspective" towards their partner. In Buber's perspective, the husband and wife relationship could be said to be in the I-Thou pattern before the conflict. Husbands or wives see their partner as a self-image of their existence as a person, but the family crisis leads them to the I-It pattern, which sees partners as things. The crisis impacts changing the pattern of relations from integrative relationships to segregative and separate ones. The separation between husband and wife begins with self-construction by the "strong" party to their partner, who is in an inferior position. This negative self-construction creeps into a social construction, which impacts the stigmatization of the inferior as the party to blame—this stigma against a partner as "It" facilitates the separation process that leads to divorce.